Evaluation of microencapsulated organic acids and botanicals on growth performance of nursery and growing-finishing pigs. Issue 4 (18th October 2021) - Hutchens, Wade M; Tokach, Mike D; Woodworth, Jason C; DeRouchey, Joel M; Goodband, Robert D; Gebhardt, Jordan T; Calderon, Hilda I; Keppy, Kaylee; Maynard, Philip; Grilli, Ester
Abstract: A total of 1, 215 pigs (L337 × 1050, PIC, Hendersonville, TN) were used to determine the effect of microencapsulated organic acids and botanicals (MOB; AviPlus; Vetagro, Inc. Chicago, IL), on growth performance from weaning to market. Pigs were weaned at approximately 21 d of age and placed in pens based on initial body weight (BW) with 27 pigs per pen in a randomized complete block design. During the 42-d nursery period, pigs were allotted to one of two treatments in an unbalanced treatment structure with 15 pens (replications) fed the control diet and 30 pens (replications) fed diets containing 0.30% MOB from days 0 to 21 and 0.10% from days 21 to 42. On day 42, pigs were transported as intact pens from the nursery to the finishing facility. During the finishing period, three treatments were applied which included: 1) pigs on the control diet in nursery remained on control diets; 2) 50% of pigs provided MOB in nursery were then fed 0.05% MOB throughout finishing, and 3) 50% of pigs provided MOB in nursery were then fed the control diet throughout finishing. All pens of pigs on treatments 2 and 3 were allotted based on ending nursery BW to the finishing treatment. There were 15 replications per treatment in the finishing period. From days 0 to 21, pigs fed diets with MOB had a tendency for increased ( P < 0.058) gain:feed (G:F) when compared to pigs fed the control diet; however, there was no evidence of difference ( P > 0.05) for average daily gain (ADG), average daily feed intake (ADFI), or day 21 BW. From days 21 to 42, there was no evidence of difference ( P > 0.05) for ADG, ADFI, or G:F. For the overall nursery period (days 0 to 42), pigs fed diets with MOB had increased ( P < 0.05) G:F (660 vs. 670 g/kg) when compared with pigs fed the control diet, but there was no evidence of difference ( P > 0.05) for day 42 BW, ADG, or ADFI between treatments. From d 42 to 106, there was no evidence of difference ( P > 0.05) for ADG, ADFI, and G:F. For the overall finishing period (days 42 to 156) and overall experimental period (days 0 to 156), there was no evidence of difference ( P > 0.05) for BW, ADG, ADFI, or G:F. For mortality and removals, there was no evidence of difference ( P > 0.05) observed during the nursery, finishing, or overall. In summary, providing MOB during the nursery phase increased G:F in the early and overall nursery phase, but there was no effect on overall wean-to-finish performance.